2014
DOI: 10.1371/journal.pone.0088957
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Differences in Mid-Adolescents in Error Monitoring and Post-Error Adjustment

Abstract: A number of studies have concluded that cognitive control is not fully established until late adolescence. The precise differences in brain function between adults and adolescents with respect to cognitive control, however, remain unclear. To address this issue, we conducted a study in which 185 adolescents (mean age (SD) 14.6 (0.3) years) and 28 adults (mean age (SD) 25.2 (6.3) years) performed a single task that included both a stimulus-response (S-R) interference component and a task-switching component. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 59 publications
(121 reference statements)
1
22
0
Order By: Relevance
“…Seemingly conflicting reports of increasing (Adleman et al, 2002; Fitzgerald et al, 2010; Rubia et al, 2006, 2007), decreasing (Durston et al, 2002; Tamm et al, 2002) or unchanging (Casey et al, 1997; Konrad et al, 2005; Marsh et al, 2006; Rodehack et al, 2014) pMFC response to task demands across prior studies may result from the use of different fMRI probes. For example, probes of cognitive interference compared to response inhibition engage overlapping (Chambers et al, 2009; Simmonds et al, 2008;Wager et al, 2005), yet distinct (Bari and Robbins, 2013;Van Velzen et al, 2014) elements of task control and it is possible that distinguishable neural networks with unique maturational trajectories may underlie the development of these task control sub-process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Seemingly conflicting reports of increasing (Adleman et al, 2002; Fitzgerald et al, 2010; Rubia et al, 2006, 2007), decreasing (Durston et al, 2002; Tamm et al, 2002) or unchanging (Casey et al, 1997; Konrad et al, 2005; Marsh et al, 2006; Rodehack et al, 2014) pMFC response to task demands across prior studies may result from the use of different fMRI probes. For example, probes of cognitive interference compared to response inhibition engage overlapping (Chambers et al, 2009; Simmonds et al, 2008;Wager et al, 2005), yet distinct (Bari and Robbins, 2013;Van Velzen et al, 2014) elements of task control and it is possible that distinguishable neural networks with unique maturational trajectories may underlie the development of these task control sub-process.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies treated age continuously, enabling the detection of more subtle age-related variations. Yet, while several such studies have tested for simple linear effects of age (Adleman et al, 2002; Casey et al, 1997; Durston et al, 2002; Fitzgerald et al, 2010; Konrad et al, 2005; Rodehack et al, 2014; Rubia et al, 2006, 2007; Tamm et al, 2002; but see Marsh et al, 2006), none have reported non-linear (e.g., quadratic or U-shaped) effects of age on brain activation in response to task control demands. Given recent evidence suggesting that developmental change in cortical thickness (including in pMFC) follows a non-linear trajectory (Lenroot and Giedd, 2006), it is possible that a non-linear fit may characterize developmental changes in pMFC engagement by task control.…”
Section: Introductionmentioning
confidence: 99%
“…Details of baseline data and a list of the entire exclusion criteria can be found elsewhere (Rodehacke et al . ). Subjects participated in the study after giving written informed consent for each acquisition.…”
Section: Methodsmentioning
confidence: 97%
“…In line with a previous publication concerning this task (Rodehacke et al . ), we predict that over time (1) RT and (2) errors decrease, whereas (3) brain responses in core cognitive control areas (ACC, dlPFC, pre‐SMA and PPC) increase.…”
Section: Introductionmentioning
confidence: 99%
“…In health, the neural correlates of error-related processing typically encompass a network of regions of the medial prefrontal cortex (PFC) including the anterior cingulate cortex (ACC) [35]. Despite this common neural signature, error-related processing is also modulated by individual differences [69]. That is, certain individuals or groups may differ in the frequency with which they commit errors, and/or in the reactivity they show upon committing such errors.…”
Section: Introductionmentioning
confidence: 99%